ANALISIS MAQASID SYARIAH JASSER AUDA TERHADAP COUNTER LEGAL DRAFT KOMPILASI HUKUM ISLAM - Muhammad Ali Murtadlo (Fakultas Syariah IAIN Ponorogo, 2021)
Islamic law transformative bid is made to replace the Islamic Law Compilation (KHI) in the form of Counter Legal Draft Compilation of Islamic Law (CLD-KHI), attracted the attention of academics, scholars and jurists of Islam in Indonesia. Many of those who reject and not infrequently also agree with the offer. This formulation is a challenge to bring order to respect Indonesia by Islamic law to all national character, culture and progress in democratization and upholding human rights, including women's rights. This study aims to answer the question (a) how is the legal istinbath method used in formulating the Counter Legal Draft Compilation of Islamic Law? (b) What is the formulation of the Counter Legal Draft Compilation of Islamic Law from the perspective of Jasser Auda's sharia maqasid? Library research using qualitative approach suggests that (a) the CLD-KHI is a legal draft in the form of provisions, so that in the process of its formulation is done through a procedural step that is done gradually, systematically, and involve several competent authority (b) Formulation of family law Islam offered in CLD-KHI in law istinbath method is not contrary to the concept of maqasid syariah Jasser Auda. However, the application instead of KHI still hindered political factor, because there are chapters that are considered controversial.